Prism adaptation changes resting-state functional connectivity in the dorsal stream of visual attention networks in healthy adults: A fMRI study. (October 2019) - Tsujimoto, Kengo; Mizuno, Katsuhiro; Nishida, Daisuke; Tahara, Masatoshi; Yamada, Emi; Shindo, Shiori; Kasuga, Shoko; Liu, Meigen
Abstract: Unilateral spatial neglect (USN) can be defined as a failure to orient to contra-lesional stimuli in the absence of either sensory or motor defects. Although the behavioral and clinical effects of prism adaptation (PA) are widely accepted, its underlying mechanisms are still controversial. However, recent neuroimaging and neurophysiological studies support the idea that PA affects the visual attention and sensorimotor networks including in the parietal cortex and cerebellum. We investigate the effect of PA on functional connectivity (FC) in attention and sensorimotor networks, evaluating changes of resting-state FC before and after PA in healthy individuals using functional magnetic resonance imaging (fMRI). MR sessions were conducted before PA, after PA (Post1), and 1 h after PA (Post2). The FC between the right frontal eye (FEF) field and the right intraparietal sulcus was significantly decreased at Post1 and that between the right FEF and the right anterior cingulate cortex was significantly increased after PA and recovered within 1 h. This is the first study to demonstrate transient changes of resting-state FC in the right dorsal attention network (DAN) by PA in healthy adults using fMRI. These results will contribute to the elucidation of the underling mechanism of PA therapy and to devising new therapies for USN and/or other higher cortical dysfunctions.